Pelatihan Penulisan Karya Inovatif E-Modul dalam Rangka Pengembangan Keprofesian Berkelanjutan - Setiawan, Yayan Eryk Setiawan; Triwilujeng Ayuningtyas (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
Teachers need to follow Continuing Professional Development (CPD) to improve their competence. This CPD can be carried out on a community basis through Subject Teacher Consultation (STC). One of the STCs who are partners in this community service activity is the STC Mathematics MTs Lumajang Regency. However, the partners have not carried out the third CPD activity, namely the creation of innovative works. This has an impact on the student's low activity and result of study. This problem can be overcome by providing training for these teachers. Therefore, this service activity aims to improve the ability of teachers to create innovative works e-modules. This service activity consists of 3 stages, namely training, group work, and evaluation. The results of the service show that teachers understand the important role of CPD and all groups have been able to create innovative e-modules. The results of the dedication evaluation show that the success rate of e-module creation training is 89.50%, which means it is very successful.